2003
DOI: 10.1002/adma.200304692
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Electroluminescence from Lanthanide Tetraphenylporphyrin:Polystyrene Blends

Abstract: the effect of morphology on the transistor performance of Me 4 PENT is underway and will be reported in a future publication.In conclusion, a pentacene derivative, Me 4 PENT, has been successfully synthesized and single crystals of Me 4 PENT were obtained by gradient sublimation. Calculations show that Me 4 PENT has similar reorganization energy to that of pentacene. TFTs fabricated with Me 4 PENT showed a higher charge transport mobility with the bottom-contact mode device prepared with a deposition substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…[5c] Kang et al [6] reported a polystyrene-Nd III complex blend that showed photoluminescence in solution between l = 850 and 1150 nm with a photoluminescence quantum yield F PL of 0.0024. Although lanthanide complexes are interesting owing to their sharp f-f emission band, their F PL values in the red-NIR region are usually low (F PL < 0.005), and thereby their use as emitting phosphors is still limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5c] Kang et al [6] reported a polystyrene-Nd III complex blend that showed photoluminescence in solution between l = 850 and 1150 nm with a photoluminescence quantum yield F PL of 0.0024. Although lanthanide complexes are interesting owing to their sharp f-f emission band, their F PL values in the red-NIR region are usually low (F PL < 0.005), and thereby their use as emitting phosphors is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Although a wide plethora of examples can be found in which quantum dots, [2] ZnO, [3] polyoxometalate, [4] or rare-earth cations [5] are incorporated into polymers to act as emitting phosphors, there is a lack of Abstract: The embedding of functional inorganic entities into polymer matrices has become an intense field of investigation in which the main challenges are to keep the added value of the inorganic entities while preventing their self-aggregation within the organic matrix. We present a simple way to obtain a homogeneous highly red-NIR luminescent hybrid copolymer that contains covalently bonded nanometric-sized {Re 6 cluster complexes are primarily functionalized in two steps with tert-butylpyridine (TBP) and methacrylic acid (MAC) to give neutral [Re 6 Se 8 A C H T U N G T R E N N U N G (TBP) 4 A C H T U N G T R E N N U N G (MAC) 2 ] building blocks that are copolymerized with methyl methacrylate (MMA) either in solution or in bulk in the presence of azobisisobutyronitrile as an initiator. Several samples containing 0, 0.025, 0.05, and 0.1 wt % of functionalized {Re 6 } clusters were prepared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nonconjugated polymers, such as poly(methylmethacrylate)(PMMA), 11,14,15 polystyrene, 13,16,17 and polyvinyl alcohol, 18 have been applied in conjugated polymer blends to improve the performance of the LEDs. Ethyl-cyanoethyl cellulose [(E-CE)C] is a semirigid molecule with its good properties for forming thin film, good transparency in the visible range, and large band gap.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In most cases, luminescent lanthanide complexes consist of a lanthanide ion and a chelating luminescent ligand which acts as a sensitizer that transfers excitation energy to the encapsulated lanthanide ion. The presence of the luminescent ligand overcomes the lanthanide ion's intrinsically low luminescence intensity by direct excitation of the lanthanide ion with low absorption and emission cross-sections.…”
mentioning
confidence: 99%